(untitled) (Journal of the College of Basic Education, 2022)
It is certain that there are features specific to the means of communication, and thanks to them, it has become a distinguished influence on the lives of those who are exposed to it. It appears simultaneously and another percentage will have long-term and cumulative subsequent effects related to behavior.